2018
DOI: 10.3390/foods7030032
|View full text |Cite
|
Sign up to set email alerts
|

Increased Effectiveness of Microbiological Verification by Concentration-Dependent Neutralization of Sanitizers Used in Poultry Slaughter and Fabrication Allowing Salmonella enterica Survival

Abstract: Sanitizer neutralizers can assist foodborne pathogen detection during routine testing by counteracting sanitizer residues carried over into fluids collected and tested from food samples. This study tested sanitizer-matched neutralizers applied at increasing concentrations to facilitate Salmonella enterica survival following exposure to cetylpyridinium chloride (CPC) or peracetic acid (PAA), identifying minimum required concentrations of neutralizers to facilitate pathogen survival. Salmonella isolates were ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…7,8 Dey and Engley 9 previously incorporated lecithin into an antimicrobial neutralization formula for the purposes of counteracting QAC-type sanitizers. Mohammad et al 10 reported that the incorporation of soy lecithin at 7.0 g/L effectively neutralized CPC (0.8% w/v), facilitating Salmonella detection in a model microbiological medium.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Dey and Engley 9 previously incorporated lecithin into an antimicrobial neutralization formula for the purposes of counteracting QAC-type sanitizers. Mohammad et al 10 reported that the incorporation of soy lecithin at 7.0 g/L effectively neutralized CPC (0.8% w/v), facilitating Salmonella detection in a model microbiological medium.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial populations may also be further reduced by residual exposure to antimicrobial compounds that may be dispersed during the rehydration process. Addition of neutralizing agents including sodium thiosulfate and lecithin are included in diluents used for poultry carcass sampling and environmental sampling, as they act to bind residual sanitizers (Mohammed et al, 2018). Sodium thiosulfate was required to allow for growth of different S. enterica serotypes when challenged with peracetic acid, which decomposes into acetic acid and peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…On days 0, 7, 14, and 21, treated frankfurters were removed from refrigeration (4 °C) and stomached for 1 min at 200 rpm in 100 mL of nBPW [ 29 ] so that injured, viable bacteria and biofilm-forming bacteria could be recovered without the continued action of the antimicrobials [ 30 , 31 ]. The resulting homogenates were diluted 10 −1 to 10 −6 , and were enumerated via direct plating methodology where 100 μL of the diluted homogenates were spread plated on Oxford agar in duplicate.…”
Section: Methodsmentioning
confidence: 99%